Capacitance-Voltage and Current-Voltage Characteristic for Multi- Walled Carbon Nanotubes Grown in Oxygen Atmosphere - Al-Essa, Izzat M. (Iraqi Journal of Physics, 2009)
Carbon nanotubes were prepared by an arc-discharge method,under different values of pressure of oxygen gas. The structure ofmulti-walled carbon nanotubes powders has been characterized bylow-angle X-ray diffraction .The morphology of carbon nanotubepowder was examined by transmission electron microscope. Thecapacitance-voltage and current- voltage (dark and illuminationcurrent) characterization were measured under different values ofpressure (10-3, 10-4, 10-5) mbar of oxygen gas